2014
DOI: 10.1016/j.jinorgbio.2014.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of nuclear receptor function by cellular redox poise

Abstract: Nuclear receptors (NRs) are ligand-responsive transcription factors involved in diverse cellular processes ranging from metabolism to circadian rhythms. This review focuses on NRs that contain redox-active thiol groups, a common feature within the superfamily. We will begin by describing NRs, how they regulate various cellular processes and how binding ligands, corepressors and/or coactivators modulates their activity. We will then describe the general area of redox regulation, especially as it pertains to thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 184 publications
(177 reference statements)
0
13
0
Order By: Relevance
“…It was shown that REV-ERBb harbors a regulatory disulfide bond in the heme-binding pocket, which dictates the binding of the cofactor and thus the activation of the TF (Gupta and Ragsdale 2011). Although these cysteine residues are not conserved in the closely related REV-ERBa, a similar mechanism might still be in place to control this TF because redox regulation appears to be a common theme in the biology of the nuclear receptor superfamily (Carter and Ragsdale 2014).…”
Section: Redox Control Over the Negative Arm Of The Ttflmentioning
confidence: 99%
“…It was shown that REV-ERBb harbors a regulatory disulfide bond in the heme-binding pocket, which dictates the binding of the cofactor and thus the activation of the TF (Gupta and Ragsdale 2011). Although these cysteine residues are not conserved in the closely related REV-ERBa, a similar mechanism might still be in place to control this TF because redox regulation appears to be a common theme in the biology of the nuclear receptor superfamily (Carter and Ragsdale 2014).…”
Section: Redox Control Over the Negative Arm Of The Ttflmentioning
confidence: 99%
“…Over 300 different proteins (Go et al, ; Pan et al, ) are known to be subject to changes in functional activity as a consequence of Cys oxidation/reduction processes. This includes mitochondrial proteins (Mailloux, Jin, & Willmore, ), signaling systems (Ray, Huang, & Tsuji, ; Forman, Ursini, & Maiorino, ), and nuclear hormone receptors involved in transcriptional activities (Carter & Ragsdale, ). Such Cys oxidation processes seem to constitute a PTM network that shows complexity and reversibility that might rival other PTM systems such as phosphorylation.…”
Section: A Brief Redox Code Primermentioning
confidence: 99%
“…The multiple functions of NRs (DNA, ligand, and coregulator binding) are accomplished through their modular structure (22,23). The N-terminal A/B domain is hypervariable, is involved in ligand-independent transcriptional regulation, and is subject to phosphorylation.…”
mentioning
confidence: 99%